Progress of ultra-high-field superconducting magnets in China. (30th December 2021) - Wang, Qiuliang; Liu, Jianhua; Zheng, Jinxing; Qin, Jinggang; Ma, Yanwei; Xu, Qingjin; Wang, Dongliang; Chen, Wenge; Qu, Timing; Zhang, Xingyi; Jiang, Donghui; Wang, Yaohui; et al.
Abstract: High magnetic fields play a critical role in the development of modern science and technology, breeding many significant scientific discoveries and boosting the generation of new technologies. In the last few years, China has undertaken a great deal of work on the application of ultra-high-field (UHF) superconducting magnet technology, such as for the Synergetic Extreme Condition User Facility in Beijing, the UHF nuclear magnetic resonance/magnetic resonance imaging, nuclear fusion energy, particle accelerator, and so on. This paper reports the research status of UHF superconducting magnets in China from different perspectives, including design options, technical features, experimental progress, opportunities, and challenges.